Effects of Dexmedetomidine on Postoperative Pain and Recovery Time in Obese Patients. (28th September 2022) - Zhang, Qian; Zhang, Zhaojian; Wang, Bing; Zhao, Chao; Xu, Yuedan
Abstract : Objective . The objective of this study is to investigate the effect of dexmedetomidine on postoperative pain and recovery time in obese patients. Methods . A total of 100 obese patients with body mass index BMI ≥ 30 kg/m 2 who underwent laparoscopic sleeve gastrectomy under general anesthesia in our hospital from January 2019 to December 2021 were included and assigned into DEX group (dexmedetomidine group) and NS group (normal saline group). The bariatric surgery patients who were given normal saline pump were the NS group (n = 50 ), and the bariatric surgery patients who were given the dexmedetomidine pump were the DEX group (n = 50 ). The patients in the DEX group were given continuous intravenous infusion of dexmedetomidine before, during, and after induction of anesthesia at a dose of 0.4 μ g. kg-1. h-1, 0.4 μ g·kg-1. h-1, 0.2 μ g·kg-1. h-1, respectively. The NS group was infused with the same volume of normal saline for the same time. The two groups of patients were treated with the same anesthesia induction and maintenance program. By comparing the operation, anesthesia, postoperative extubation, and recovery time of the two groups of patients, the effect of dexmedetomidine on the postoperative recovery time of obese patients was analyzed. Visual analogue scale (VAS) and adverse reactions were compared to analyze the effect of dexmedetomidine on postoperative pain in obese patients. Results. The operation, anesthesia, postoperative extubation, and recovery time of the DEX group were significantly lower than those of the NS group, whereas the VAS and adverse reactions were significantly lower than those in the NS group (P < 0.05 ). Conclusion . An appropriate dose of dexmedetomidine in bariatric surgery for morbidly obese patients can effectively shorten the recovery time and extubation time of patients, reduce postoperative pain and the incidence of adverse reactions, and is worthy of clinical application. Dexmedetomidine 2 μ g/kg has promising anesthesia benefits in bariatric surgery of obese patients, can provide favorable analgesia and quality of recovery, help reduce the degree of stress response of patients, and does not increase the risk of adverse events. However, this study has certain limitations, so physicians should tailor the dosage according to the patient's physical condition in clinical practice.